2022
DOI: 10.1038/s41598-022-24618-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimized APPS-tDCS electrode position, size, and distance doubles the on-target stimulation magnitude in 3000 electric field models

Abstract: Transcranial direct current stimulation (tDCS) is a widely used noninvasive brain stimulation technique with mixed results to date. A potential solution is to apply more efficient stimulation to ensure that each participant receives sufficient cortical activation. In this four-part study, we used electric field (E-field) modeling to systematically investigate the cortical effects of conventional and novel tDCS electrode montages, with the goal of creating a new easily adoptable form of tDCS that induces higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
2
19
0
Order By: Relevance
“…Our findings about peak EF within the frontopolar cortex are in line with a previous modeling study that reported strong EF intensity within the medial prefrontal cortex (MPFC) rather than DLPFC in all commonly used bipolar DLPFC electrode montages in depression (Csifcsák et al, 2018). This study suggested that symptom improvement in DLPFC tES trials in depression might not necessarily be specifically related to the DLPFC and other brain areas with strong EF (e.g., MPFC) may also contribute to the tES treatment outcomes (Csifcsák et al, 2018). In line with this assumption, preliminary evidence from clinical trials confirmed associations between EF strength and behavioral changes in depression (Suen et al, 2021).…”
Section: Dlpfc Montages Make Peak Ef In Frontopolar Areassupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings about peak EF within the frontopolar cortex are in line with a previous modeling study that reported strong EF intensity within the medial prefrontal cortex (MPFC) rather than DLPFC in all commonly used bipolar DLPFC electrode montages in depression (Csifcsák et al, 2018). This study suggested that symptom improvement in DLPFC tES trials in depression might not necessarily be specifically related to the DLPFC and other brain areas with strong EF (e.g., MPFC) may also contribute to the tES treatment outcomes (Csifcsák et al, 2018). In line with this assumption, preliminary evidence from clinical trials confirmed associations between EF strength and behavioral changes in depression (Suen et al, 2021).…”
Section: Dlpfc Montages Make Peak Ef In Frontopolar Areassupporting
confidence: 92%
“…Similarly, another single-subject simulation study, which employed atlas-based parcellation, showed that maximum values of tangential and normal components of EFs in DLPFC stimulation were situated in the orbital and frontopolar cortices when electrodes were placed over F3-Fp2 (Callej on-Leblic & Miranda, 2020). In group-level analyses, Csifcsak et al also found that in commonly used bipolar DLPFC montages for depression, strong EFs were not only present in DLPFC but also in the medial prefrontal cortex (MPFC) (Csifcsák et al, 2018), which has been suggested as a new target for depression in TMS studies (Diederichs et al, 2021;Juckel et al, 1999). In addition, a network-led approach indicated that, although DLPFC is a component of the executive control network, the limbic network received the highest EFs in both symmetric and asymmetric DLPFC tES montages .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For tES, we simulated the following four montages ( Figure 1 ). (1) APPS-tES consisting of two rectangular 1 by 1 cm electrodes, with the anode placed over CP3 and the cathode over FC3 [4]. (2) Bilateral tES consisting of two rectangular 5 by 5 cm electrodes, with the anode placed over C3 and the cathode over C4 [38].…”
Section: Methodsmentioning
confidence: 99%
“…By doing so, E-field modeling provides a potent tool to individually examine the effects of noninvasive brain stimulation and to address the high variability in efficacy that is currently observed across individuals. In the past, E-field modeling has already helped researchers derive novel tES montages and identify dose-response relationships [3][4][5][6][7][8], has suggested optimal stimulation targets in clinical cohorts [9,10], and has pinpointed which cortical regions are being stimulated by TMS [11]. In recent years, the introduction of software packages such as SimNIBS and ROAST has catalyzed the widespread use of E-field modeling [1,2].…”
Section: Introductionmentioning
confidence: 99%